Concoradance of clinical and neurophysiologic diagnoses of carpal tunnel syndrome - Martić, Vesna V (Vojnosanitetski pregled, 2015)
Introduction/Aim. Clinical presentation and neurophysiological examination are crucial in diagnosing carpal tunnel syndrome (CTS). The aim of this study was to determine sensitivity and specificity of clinical examination for diagnosing of CTS in relation to neurophysiological evaluation. Methods. The sample included 181 patients referred to the neurologist for further diagnosis of pain and parestesias in the arm (81 women and 100 men mean age 42 ± 14 years and 52 ± 16 years, respectively). All the patients were neurophysiologicly tested. Results. Out of 181 patients, clinical findings were considered positive for CTS in 37 patients. The neurophysiological findings for CTS were positive in 60 patients. Both clinical and neurophysiological findings were positive in 31 patients and both findings were negative in 115 patients (sensitivity 0.51; specificity 0.95). Conclusion. Low sensitivity and high specificity suggest that it is easier to exclude rather than to accurately diagnose CTS based on clinical examination alone. Thus, there is the need for neurophysiological evaluation of patients with complains in the arm.
Keywords: carpal tunnel syndrome; diagnosis; signs and symptoms; sensitivity and specificity